Strengthening Al-Islam and Kemuhammadiyahan (AIK)-Based Character Education (PPK) during the Covid-19 Pandemic at Muhammadiyah Elementary School Nitikan Yogyakarta - Yusutria, Yusutria; Yuzarion, Yuzarion; Kholifah, Nisa Amalia; Al-Husna, Yasmin Syarifah; Alfikri, Ikhsan; Febriana, Rina (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
Character education occupies a central role in the world of education which is a constitutional mandate. The progress of science and technology that is unstoppable by physical strength with its various positive and negative impacts, is a strong reason to make character education the basis for an ethical defense in the face of the negative impacts of globalization, especially during the pandemic. The role of character education is a very big concern in Muhammadiyah educational institutions, especially AIK subjects, character education is important in every learning process in an effort to achieve Muhammadiyah educational goals and organizational goals. The purpose of this study was to determine the strengthening of AIK-based character education (PPK) during the covid-19 pandemic. The research method used is quantitative with a survey method. The number of samples in this study was 150 parents of students. Collecting information using a survey method with a Likert scale. Information analysis by calculating the percentage of information on each indicator, then interpreting the percentage score information and analyzed descriptively on each indicator. The results of this study showed 91.8% with very good criteria on strengthening character education (PPK) based on Al-Islam and Muhammadiyah during the covid-19 pandemic at Muhammadiyah Elementary School Nitikan Yogyakarta